The Influence Of Knowledge, Involvement, And Trust On Customer Decisions At Sutan Raja Hotel In Palu City - Moh.Yusril Anugrah; H.Syamsul Bahri Dg; Elimawaty Rombe; Cici Rianty K (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to examine the influence of knowledge, involvement, and trust on customer decisions to stay at Sutan Raja Hotel in Palu City. The target population consists of guests who have previously stayed at the hotel. The sampling technique used was purposive sampling, resulting in a total of 82 respondents. Data were collected through a structured questionnaire and analyzed using multiple regression analysis. The findings reveal three key points. First, knowledge, involvement, and trust simultaneously have a significant effect on customer decision-making when choosing to stay at Sutan Raja Hotel. Second, when examined individually, knowledge does not have a significant influence on customer decisions. Third, both involvement and trust show a significant partial influence on customers’ decisions to stay at the hotel. These results suggest that while customers may not prioritize knowledge or information about the hotel when making their decision, their level of involvement and the trust they place in the hotel play a crucial role. This implies that building strong customer relationships and trust, as well as encouraging customer engagement, are essential strategies for increasing customer retention and satisfaction in the hospitality industry.